GALERI SENI LUKIS BANJARBARU - Rahmah, Annisa; Muchamad, Bani Noor (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Art galleries have a role as a means for artists to exhibit their work and a means for the public to enjoy and obtain information about art on a non-formal basis. Galleries cannot be passive institutions that only provide space for art collections, but must also provide space for the public to "interact" with art collections and make a strong impression. Through the concept of collective memory and the combined metaphor method, it is hoped that it will be able to provide a strong, deep and informative impression for visitors. The application of these concepts and metaphors focuses on building exteriors, interiors and landscapes to create an impression on visitors through visuals so that the goal of educating the public through architecture is achieved.